Determinación de cisticercosis en cerdos faenados en el camal municipal del cantón Ventanas, Provincia de Los Ríos - Triana Vera, Andy Walter (2024)
The objective of this study was to determine the presence of cysticercosis in pigs slaughtered in the municipal slaughterhouse of the Ventanas canton, Province of Los Ríos. Porcine cysticercosis, caused by the larva of Taenia solium, is a zoonotic disease of public health importance and with a significant socioeconomic impact. During the study period, 288 samples from slaughtered pigs were analyzed, macroscopically examining the organs and tissues affected by cysticercosis, such as the tongue, masseter muscles, intercostal muscles, femoral muscles, heart and liver. The results revealed a total absence of positive cases of cysticercosis, which translates into an incidence of 0% for all the variables studied, including sex, age, origin, affected organs and tissues. In addition, surveys were conducted with pig farmers to detail the factors associated with the presence of cysticercosis and thus identify the prevention practices implemented in pig facilities. The results pointed to areas for improvement in implementing quarantine protocols for newly arrived pigs, controlling human access to the facilities, and continuously training staff on biosecurity and disease prevention practices. In conclusion, the presence of cysticercosis was not detected in the pigs slaughtered in the municipal slaughterhouse of the Ventanas canton during the study period. However, it is essential to maintain and reinforce sanitary and hygiene control measures in swine facilities, as well as carry out continuous monitoring of cysticercosis and its associated factors to guarantee food security and public health in the region.